2022
DOI: 10.1186/s12964-022-01006-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of biological pathways and processes regulated by NEK5 in breast epithelial cells via an integrated proteomic approach

Abstract: Specific members of the Nima-Related Kinase (NEK) family have been linked to cancer development and progression, and a role for NEK5, one of the least studied members, in breast cancer has recently been proposed. However, while NEK5 is known to regulate centrosome separation and mitotic spindle assembly, NEK5 signalling mechanisms and function in this malignancy require further characterization. To this end, we established a model system featuring overexpression of NEK5 in the immortalized breast epithelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…Additionally, Cyclophilin-D (CypD) can directly interact with TFB2M to inhibit mtDNA transcription [ 113 ]. Ferezinwe and colleagues employed various MS-based proteomic approaches to investigate the interactome of Nima Related Kinases 5 (NEK5) [ 114 ]. Their study uncovered the association between NEK5 and mitochondrial proteins, such as TFAM, TFB2M, and MFN2, suggesting their potential involvement in mitochondrial maintenance, transcription, and repair processes [ 114 ].…”
Section: Dysregulation Of Mitochondrial Transcription Affects Tumor P...mentioning
confidence: 99%
“…Additionally, Cyclophilin-D (CypD) can directly interact with TFB2M to inhibit mtDNA transcription [ 113 ]. Ferezinwe and colleagues employed various MS-based proteomic approaches to investigate the interactome of Nima Related Kinases 5 (NEK5) [ 114 ]. Their study uncovered the association between NEK5 and mitochondrial proteins, such as TFAM, TFB2M, and MFN2, suggesting their potential involvement in mitochondrial maintenance, transcription, and repair processes [ 114 ].…”
Section: Dysregulation Of Mitochondrial Transcription Affects Tumor P...mentioning
confidence: 99%
“…Nek5 was shown to interact with COX11, an intrinsic mitochondrial membrane protein essential for the assembly of an active cytochrome c oxidase complex (complex IV) in a yeast two-hybrid screening [ 16 ]. In 2022, an analysis of Nek5-overexpressing MCF10A cells proteome using BioID revealed interesting mitochondrial partners such as HIGD1A, TFAM, C2orf47, SLC25A12, GSR, TIGAR, IARS2, IDH3B, CLPX, TFB2M, MFN2, PPA2, MRPS11, and MT-ATP6 (from the highest to the lowest logFC, p -value < 0.05) [ 18 ]. The interactome enrichment pathway analysis of NEK5 interactors showed that mitochondrial organization and mitochondrial gene expression are among the top five enriched pathways in MCF10A Nek5-overexpressing cells, reinforcing our hypothesis of Nek5 participation in mitochondrial mtDNA homeostasis and mitochondrial functions ( Figure 1 and Figure 3 ).…”
Section: Neks and The Mitochondrial Metabolismmentioning
confidence: 99%
“…Indeed, participation in DNA damage response, alternative splicing, and cilia formation has already been described for several members of the Nek family (for review, see [ 9 , 10 , 11 ]) [ 12 , 13 ]. A mitochondrion-related function was first shown for Nek1 [ 14 , 15 ], and from that, it was extended to other members: Nek5 [ 16 , 17 , 18 ], Nek10 [ 19 ], Nek4 [ 13 , 20 ], and Nek6 [ 20 , 21 ], so far.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MS-based proteomic analyses were undertaken on control and shRNA#1-mediated NRBP1 knockdown MDA-MB-231 cells. NRBP1 knockdown was induced by 1 µg/ml doxycycline for 48 h. These analyses were performed in triplicate on independent biological replicates according to previously-published protocols [21,46].…”
Section: Mass Spectrometry-based Proteomic Screenmentioning
confidence: 99%